Toxoplasma gondii infection in European mouflons (Ovis musimon) and captive wild felines from Puebla, México. (December 2020) - Valenzuela-Moreno, Luis Fernando; Cedillo-Peláez, Carlos; Rico-Torres, Claudia Patricia; Hernández-Rodríguez, María Alejandra; Carmona-Muciño, María del Carmen; Farfán-Morales, José Eduardo; Correa, Dolores; Caballero-Ortega, Heriberto
Abstract: The presence of Toxoplasma gondii in zoos is cause of alert because many susceptible species kept in captivity die of clinical toxoplasmosis. Moreover, excretion of T. gondii oocysts by infected captive wild felines into the facilities could pose a risk to workers. Herbivores in wild collections can serve as sentinels of local transmission, since they get infected by the consumption of oocysts present in ground or water. Both herbivores and felids may reveal the parasite variants which are circulating in the region. We determined the seroprevalence of T. gondii in European mouflons (n = 55) and wild felines (n = 15) from a private zoological collection located in the Eastern region of México, as well as the incidence in 41 of the mouflons using ELISA. The prevalence of T. gondii in mouflons was 14.5% (n = 55) and 17.1% (n = 41) in 2011 and 19.5% in 2012. The estimated incidence was 9.8%–12.2%. In wild felines the frequency was 80%. Four sero-positive animals (two mouflons and the two oldest African lions) were euthanized. Histopathology, conventional PCR (for B1 and SeqRep529 loci) and molecular characterization were carried out. All euthanized animals were positive to T. gondii by PCR. We identified a triple infection (I + II + III) in the brain of a mouflon. In conclusion, a high infective pressure of T. gondii in the collection was found, supported by changes in its prevalence in European mouflons. A high prevalence of infection in wild felines was determined. At least four genotypes of T. gondii are present in herbivores and carnivores, and one mouflon had a mixed infection. Graphical abstract: Image 1 Highlights: High infective pressure of T. gondii in mouflons and wild felines of a private collection in Puebla, Mexico. Four genotypes of T. gondii are present in herbivores and carnivores. A triple infection was found in one mouflon. First prospective cross-sectional study, not using serum banks.